Ultrasonic Extraction of Anthocyanins From Clitoria Ternatea Flowers Using Response Surface Methodology - Gwee Xian, Fu (2013)
This thesis deals with the anthocyanins extraction from Clitoria ternatea flowers using ultrasonic extraction with response surface methodology (RSM). The objective of this thesis were to investigate a simple, sequential and standardized method to obtain a high yield of anthocyanins from Clitoria ternatea flowers by ultrasonic extraction compared to conventional solvent extraction, evaluate the effect of extraction factors which were extraction temperature (30-50 °C), extraction time (30-150 min), ratio of liquor to solid (2-15 ml/g) and sonication power (96-240 W) on the extraction efficiency by performing first level optimization in two-level factorial design with Design Expert 7 software and measure the antioxidant activity (AA) using radical scavenging activity (RSA) method of 2,2-diphenyl-2-picrylhydrazyl (DPPH) assay. This study will benefit consumers and food industry where healthier alternatives could be introduced in their diet and into the production of food. Ultrasonic extraction using water solvent was used to extract the anthocyanins where its screening test experimental variables were optimized via Design Expert 7 software using RSM. Ultrasonic extraction showed a 246.4789 % better efficiency than conventional solvent extraction. The anthocyanins extracts exhibited a DPPH activity of 68.48 % at the optimized experimental variables. In conclusion, ultrasonic extraction is a viable extraction method for extracting anthocyanins with high antioxidant activity from Clitoria ternatea flowers. It is recommended to further optimize the screening test results in a two-level factorial design.